Clem Lloyd interviewed by Garry Sturgess in the Garry Sturgess collection. - Lloyd, C. J. (Clement John), 1939-2001.; Sturgess, Garry (1980)
Clem Lloyd talks about the Canberra Press Gallery and Prime Ministers
Recorded on 2 March 1980.
Digital master available
Summary not yet available.
Keywords: Lloyd, C. J. -- 1939-2001 -- Interviews; Canberra Press Gallery -- History; Prime ministers -- Australia